2021
DOI: 10.3389/fbioe.2021.673683
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Limitations of Myocardial Infarction Large Animal Models in Cardiovascular Translational Research

Abstract: Establishing an appropriate disease model that mimics the complexities of human cardiovascular disease is critical for evaluating the clinical efficacy and translation success. The multifaceted and complex nature of human ischemic heart disease is difficult to recapitulate in animal models. This difficulty is often compounded by the methodological biases introduced in animal studies. Considerable variations across animal species, modifications made in surgical procedures, and inadequate randomization, sample s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 167 publications
(174 reference statements)
0
36
0
1
Order By: Relevance
“…Swine models have contributed to a deeper understanding of the natural history of coronary atherosclerosis, with a valuable application to multiple research fields, such as the study of novel clinical treatment procedures efficacy (Getz and Reardon, 2012;Daugherty et al, 2017;Shin et al, 2021). The translation of results obtained in swine models to the patient situation is mainly based on intra-species comparisons of the coronary anatomy (Weaver et al, 1986;Lelovas et al, 2014), pathophysiology (Lelovas et al, 2014;Shim et al, 2016), cholesterol levels (Mahley et al, 1975) and sites of lesion formation (Shim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swine models have contributed to a deeper understanding of the natural history of coronary atherosclerosis, with a valuable application to multiple research fields, such as the study of novel clinical treatment procedures efficacy (Getz and Reardon, 2012;Daugherty et al, 2017;Shin et al, 2021). The translation of results obtained in swine models to the patient situation is mainly based on intra-species comparisons of the coronary anatomy (Weaver et al, 1986;Lelovas et al, 2014), pathophysiology (Lelovas et al, 2014;Shim et al, 2016), cholesterol levels (Mahley et al, 1975) and sites of lesion formation (Shim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several large animal models based on the use of rabbits, pigs, or non-human primates, have been adopted to e.g. : 1) study coronary atherosclerosis natural history (Getz and Reardon, 2012;Daugherty et al, 2017); 2) evaluate the efficacy of clinical treatment procedures (Shin et al, 2021); 3) identify predictive tools for the evolution of the disease, which most of the time is asymptomatic (De Nisco et al, 2020;Hoogendoorn et al, 2020;Mazzi et al, 2021). Most of the animal model-based studies on atherosclerosis onset and progression imply that their findings reliably inform human studies, sometimes suggesting a direct translation to humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several animal models of MI that include small animals such as rodents, or large animals such as swine and sheep. The pig model is an attractive choice given its similarity to humans in terms of cardiac circulatory anatomy and cardiac contraction relaxation kinetics, and cardiac output [ 41 ]. In pigs, the left coronary artery is larger and longer than the right coronary artery, as in humans.…”
Section: Animal Models For Amimentioning
confidence: 99%
“…Multiple studies have demonstrated that the inflammatory response, calcium overload and oxidative stress are involved in this complex and dynamic process and induce various modes of cardiomyocyte death ( 2 , 4 , 5 ). However, due to various reasons, such as the significant differences between animal models and AMI patients, many effective therapeutic strategies in the laboratory have been proved limited in clinical efficacy ( 5 10 ). Therefore, the underlying mechanisms and new effective therapeutic strategies are urgent to be explored.…”
Section: Introductionmentioning
confidence: 99%